Isothermal Section of Er-Mn-Nd Ternary System at 773 K - 刘敬旗 刘文军 王利娜 (Journal of rare earths, 2006)
The isothermal section of the Er-Mn-Nd ternary system at 773 K was investigated mainly by X-ray powder diffraction with the aid of differential thermal analysis. The 773 K isothermal section of the ternary system consists of 9 single-phase regions, 14 two-phase regions, and 6 three-phase regions. At 773 K, the maximum solid solubility of Er in Nd and Nd in Er is about 20%（atom fraction） Er and 26%（atom fraction） Nd, respectively. Er6Mn23 and Nd6Mn23 form a continuous solid solution. The homogeneity range of δ phase extends from about 38% （atom fraction） Er to 43% （atom fraction） Er. No ternary compounds were observed at 773 K in this system.